2016
DOI: 10.1007/s11743-016-1787-x
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Methodology to Measure the Characteristic Curvature (Cc) of Alkyl Ethoxylate Nonionic Surfactants

Abstract: This work introduces a simplified methodology for measuring the characteristic curvature (Cc) of commercial alkyl ethoxylate nonionic surfactants using carefully selected reference surfactants and oils that produce rapid and well defined separations in salinity scans. The Cc of the commercial reference surfactants was calculated using optimal salinities (S*) obtained from solubilization parameter curves, from interfacial tensions (for a selected system), and from emulsion stability tests. The latter provided a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(78 citation statements)
references
References 51 publications
12
66
0
Order By: Relevance
“…Offsets in the prediction of cloud point should be expected with the HLD because of the uncertainties in the experimental values of its parameters, particularly the value of C c . Zarate et al suggested that the minimum uncertainty on the value of C c is in the order of 0.2 HLD units (Zarate‐Muñoz et al, ). Considering the HLD equation, and the term c T being typically 0.06 HLD units °C −1 , then ±0.2 HLD units would be an equivalent of at least 3.3 °C uncertainty in cloud point predictions.…”
Section: Resultsmentioning
confidence: 99%
“…Offsets in the prediction of cloud point should be expected with the HLD because of the uncertainties in the experimental values of its parameters, particularly the value of C c . Zarate et al suggested that the minimum uncertainty on the value of C c is in the order of 0.2 HLD units (Zarate‐Muñoz et al, ). Considering the HLD equation, and the term c T being typically 0.06 HLD units °C −1 , then ±0.2 HLD units would be an equivalent of at least 3.3 °C uncertainty in cloud point predictions.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the term accounting for the surfactant hydrophobicity was called the surfactant characteristic curvature Cc . A wide database of Cc and EACN values are listed in many works by Salager, Acosta, Aubry, and Harwell [ 79 , 82 , 84 , 85 , 86 , 87 , 88 ] allowing the prediction of the HLD ( H 0 ) of several μEs.…”
Section: Modeling the Microstructure As Rationale For µE Formulatimentioning
confidence: 99%
“…All vials containing the mixtures were mixed well by hand once a day for 3 days and placed in a temperature-controlled water bath at 25 C. The S* was visually observed and determined after simultaneously shaking all the vials in the phase scan. The surfactant formulation with shortest coalescence time for each set of phase scan was defined as the S* (Budhathoki et al, 2016;Zarate-Munoz et al, 2016).…”
Section: Microemulsion Phase Behavior Studiesmentioning
confidence: 99%
“…The HLD equation was first proposed by Salager et al (1979) to describe the microemulsion phase behavior. The HLD value indicates the deviation of the surfactant formulation from the optimum condition (S*) (Acosta et al, 2008;Budhathoki et al, 2016;Zarate-Munoz et al, 2016) where an equal amount of water and oil are solubilized in the middle phase, the coalescence rate is fastest, the IFT is minimum (denoted as IFT*), and the solubilization capacity (SP) is highest (SP*). Negative, zero, and positive values of HLD correspond to Winsor Type I, III, and II microemulsions, respectively.…”
Section: Introductionmentioning
confidence: 99%